Development of Waqf-Based Halal Tourism in Indonesia: A Case Study of Teras Lembang, West Java - Ahyani, Hisam; Firdaus, Doddy Afandi; Buchori, Muhamad; Mudzakkir, Muhammad; Muadib, Ihwanul; Bhatti, Muhammad Safdar (Mazahib, 2025)
This study explores the development of waqf-based halal tourism as an innovative and sustainable model within Islamic economic law, using Teras Lembang in West Java as a case study. The primary issue identified is the limited exploration of how Islamic legal principles guide the productive use of waqf in halal tourism. Using a qualitative case study approach with normative juridical analysis, the study applies Ibn Qayyim al-Jawziyyah’s theory of legal change as a middle theory, supported by the concept of maslahah mursalah from al-Ghazālī and al-Shāṭibī, and Yusuf al-Qaradawi’s theory of halal. Data were collected through interviews, field observations, and literature review. Results show that the management of waqf-based halal tourism reflects sharia principles such as justice, transparency, and trustworthiness, while also contributing to local socio-economic empowerment through MSME growth, job creation, and increased community involvement. However, challenges such as regulatory fragmentation and low public literacy on waqf remain. This article concludes that aligning Islamic legal norms with tourism policies can enhance the legitimacy and sustainability of halal tourism. Policy recommendations include strengthening sharia supervisory institutions and integrating halal certification systems into tourism governance.